2016
DOI: 10.1159/000452246
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Pentosan Polysulfate Reduced Renal Ischemia-Reperfusion-Induced Oxidative Stress and Inflammatory Responses in an Experimental Animal Model

Abstract: Acute kidney injury (AKI) remains an independent risk factor for mortality and morbidity after vascular surgery (affecting the renal arteries) or aortic surgery (requiring suprarenal aortic clamping). These types of vascular surgery produce renal ischemia/reperfusion (I/R) injury, a common cause of AKI. The present studies aimed at monitoring the course of renal I/R injury at the cellular level and investigating the efficacy of long-term preoperative and single-shot intraoperative administration of sodium pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
4
5
0
Order By: Relevance
“…Previous studies from our lab and others have shown that PPS has potent anti-inflammatory properties in various disease models and patients (e.g., Schuchman et al 2013;Frohbergh et al 2014;Simonaro et al 2016;Hardi et al 2016;Sanden et al 2017;Hennermann et al 2016). Consistent with these reports, once weekly subQ PPS administration to MPS IIIA mice attenuated systemic inflammation, as shown by the reduction of the elevated plasma inflammatory markers IL-1a, MCP-1, MIP-1a, and G-CSF (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies from our lab and others have shown that PPS has potent anti-inflammatory properties in various disease models and patients (e.g., Schuchman et al 2013;Frohbergh et al 2014;Simonaro et al 2016;Hardi et al 2016;Sanden et al 2017;Hennermann et al 2016). Consistent with these reports, once weekly subQ PPS administration to MPS IIIA mice attenuated systemic inflammation, as shown by the reduction of the elevated plasma inflammatory markers IL-1a, MCP-1, MIP-1a, and G-CSF (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…As shown in Supplementary Fig. 2, we did observe reductions in liver or spleen GAGs in the treated mice, although we hypothesize that this is due to the remaining PPS and the fact that the drug is known to accumulate in these tissues after injection (Greenslade et al 1983). In contrast, in the spleen where less residual PPS will be present, significant GAG reductions were observed.…”
Section: Effects Of Pps Treatment On Systemic Pathology and Inflammatmentioning
confidence: 66%
“…This could be particularly relevant given that AAs are at highest risk for End Stage Renal Disease. For example, phospho-p53 has been associated with DNA damage and inflammation in rodent models of acute kidney injury and diabetic kidney disease 2932 . Higher levels of cleaved caspase 3 have also been reported in these rodent models 2931 .…”
Section: Discussionmentioning
confidence: 99%
“…Pentosan polysulphate sodium (PPS) is a nonselective anti-inflammatory agent approved by the FDA as the only oral medication for the treatment of interstitial cystitis [ 11 ]. PPS has been shown to improve renal function and fibrosis in 5/6 nephrectomized rats [ 12 ] and ischemia/reperfusion-injured rats [ 13 ]. However, whether PPS protects against diabetic renal fibrosis and the underlying mechanism by which PPS protects against renal injury remain unknown.…”
Section: Introductionmentioning
confidence: 99%